Introducing New Perspectives in the Use of Social Technologies in Learning: Social Constructionism - Parmaxi, Antigoni; Zaphiris, Panayiotis; Michailidou, Eleni; Papadima-Sophocleous, Salomi; Ioannou, Andri (My University, 2013)
Abstract This paper reports on a qualitative study of the use of social technologies, explored in the context of an intensive 650-hour Greek language course. Qualitative content analysis of instructors’ field notes, students’ and instructors’ reflections, interviews and a focus group was employed aiming at identifying the use of social technologies as a platform for constructing an online artifact. To triangulate the findings, the study also collected data by observing students’ activity with social technologies. A code scheme was developed which manifests the use of social technologies as a social constructionism platform identifying its major dimensions: exploration of ideas, construction of online artifact and evaluation of the constructed artifact. Actions within each dimension that indicate the manifestation of social constructionism are identified and discussed. This study revealed results in favor of the use of social technologies as social constructing platforms suggesting a new framework for their use.
Keywords: Social technologies; Web 2.0 technologies; Social constructionism; Online artifact